I servizi ecosistemici nella pianificazione bioregionale (2020)
After years of indiscriminate exploitation, the Anthropocene period is giving us back a nature whose reactions make the Earth less and less habitable: reversing the route has now become a urgent priority. The paradigm of ecosystem services is moving a step in the right direction in considering the multiplicity of benefits offered to mankind by the environment, but lends itself to quantitative drifts that risk extending commodification to the world of nature. This book investigates the consistency and usefulness for the sciences of the territory of the paradigm of ecosystem services from multiple disciplinary horizons, advancing the proposal to bring it back within a bioregional approach, with the introduction of the concept of eco-territorial services.